Evaluación y desempeño de la red de agua potable en la parroquia rural Toacaso. - Pallasco Yugsi, Luis Orlando (2018)
The present titration work seeks to evaluate and design the drinking water network in the Toacaso rural parish, where cadastre activities were developed in conjunction with the Drinking Water Management Board and the GADPR-T, in this approach with the authorities the Failures in the distribution network built in 2012, plus mutual support for the development of the project and obtain the solution that will start the use of this system by adding a new section to design for the Loma de Monjas neighborhood. The main objectives to solve these problems and achieve the feasible and sufficient distribution of drinking water in the parish is: to study the cadastres of the pipeline based on existing data, field trips and obtain parameters for the evaluation of the existing network, in addition to carrying out the topographic survey for the hydraulic design of the same and the new section, this analysis will be based on the current regulations published by the National Water Secretariat of Ecuador. The methodology used was an exploratory investigation between the different stages of the construction of the existing water system, where the operation and maintenance phase of the different elements that interfere in its proper functioning were considered, justifying that a redesign of the system is necessary. The network for the distribution of drinking water and that by 2047 the amount of water will not be enough even more if the population increases.